1984
DOI: 10.1159/000206413
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-Induced Hemolytic Anemia

Abstract: A patient who had recently undergone craniotomy for a meningioma experienced carbamazepine (Tegretol)-induced hemolytic anemia. To our knowledge, this is the first reported case of hemolytic anemia clearly induced by carbamazepine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Despite hemolysis caused by cationic and anionic dendrimers is reported to be generation-and concentrationdependent, non-hemolysis is found at low dendrimer concentration (<1 mg/mL) (Asthana et al, 2005;Bhadra et al, 2003;Malik et al, 2000;María Jimena Prieto et al, 2011). However, it is of importance to test the hemolytic effect of the complexes as it has been reported that CBZ can induce hemolytic anemia (Sobotka et al, 1990;Stroink et al, 1984;Yamamoto et al, 2007). In this work, we evaluated the hemolytic effects ( Figure 5) and possible morphological changes ( Figure S5) after 4-and 24-h human red blood cells incubation with free CBZ, dendrimers and D-CBZ complexes.…”
Section: Ex Vivo Toxicity: Hemolysis Assay and Human Red Blood Cells mentioning
confidence: 99%
“…Despite hemolysis caused by cationic and anionic dendrimers is reported to be generation-and concentrationdependent, non-hemolysis is found at low dendrimer concentration (<1 mg/mL) (Asthana et al, 2005;Bhadra et al, 2003;Malik et al, 2000;María Jimena Prieto et al, 2011). However, it is of importance to test the hemolytic effect of the complexes as it has been reported that CBZ can induce hemolytic anemia (Sobotka et al, 1990;Stroink et al, 1984;Yamamoto et al, 2007). In this work, we evaluated the hemolytic effects ( Figure 5) and possible morphological changes ( Figure S5) after 4-and 24-h human red blood cells incubation with free CBZ, dendrimers and D-CBZ complexes.…”
Section: Ex Vivo Toxicity: Hemolysis Assay and Human Red Blood Cells mentioning
confidence: 99%
“…In some cases, specific autoantibodies can be demonstrated. Both haemolytic and aplastic anaemia have been reported during anticonvulsant administration (Gerson et al 1983;Stroink et al 1984). Bone marrow depression is a rare adverse reaction to anticonvulsants, but is obviously important for the potentially fatal consequences.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%